Mechanisms For Attracting Foreign Investment To Free Economic Zones And Supporting Them Through Taxes - Kuziev Ravshan Ramazanovich (Global Scientific Publishing, 2025)
The article analyzes the theoretical and practical aspects of attracting foreign investment to free economic zones and supporting them through taxes. Based on international and local experience, fiscal factors affecting investment flows in free economic zones, the effectiveness of tax incentives, and institutional mechanisms are studied. Based on data for 2024, a statistical analysis of investment sources and their share in the economy is conducted, and proposals are developed to improve the investment climate. The results of the study substantiate the importance of tax policy stability, flexibility of incentives, and a diversified financing system in attracting foreign capital.
Keywords: Free economic zones; foreign investments; tax incentives